2019
DOI: 10.4028/www.scientific.net/msf.969.715
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Sunflower Oil as Dielectric Fluid in Die Sinking Electric Discharge Machining Process

Abstract: Electric Discharge Machining (EDM) is used to machine complex geometries of difficult to cut materials in the area of making dies, mould and tools. Currently, hydrocarbon based dielectric fluids are used in EDM and which plays major role for material removal and it emits harmful emission. In this work, vegetable oil is attempted as dielectric fluid and their performance are studied during processing of AISI P20 steel. The effect of pulse on time (Pon) , pulse off time (Poff), and current (A) on Material Remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Results revealed that the biodiesels offered higher MRR at top most energy settings compared to mineral oil and suggested that the biodiesels alternative to mineral oil [20]. An investigation was conducted to analyze the impact of current based parameters on response measures and found that the pulse on time had a greater impact on MRR as compared to nonelectrical parameters namely feed rate and spindle speed [21]. Surface morphology of debris particles obtained while processing SKD 11 with kerosene and eco-friendly oils at different input condition was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed that the biodiesels offered higher MRR at top most energy settings compared to mineral oil and suggested that the biodiesels alternative to mineral oil [20]. An investigation was conducted to analyze the impact of current based parameters on response measures and found that the pulse on time had a greater impact on MRR as compared to nonelectrical parameters namely feed rate and spindle speed [21]. Surface morphology of debris particles obtained while processing SKD 11 with kerosene and eco-friendly oils at different input condition was analyzed.…”
Section: Introductionmentioning
confidence: 99%